Jigsaw Model Learning for Increase Performance Study of Student Class VII MTs Negeri 2 Kendarion Materials for Designing General Statements and Stages Indonesian Subjects - RAHMATANG (International Journal of Management and Education in Human Development, 2023)
Objective main from study This is for know level performance learn Indonesian students’ class VII MTs Negeri 2 Kendariafter application of learning models Jigsaw cooperative Study. This gives benefits in increasing ability examine teachers in schools, especially for internal teachers develop learning in class through study action. The results of this study indicate that the results of learning Indonesian for class VII MTs Negeri 2 Kendari show an increase in the results of the first cycle both in groups and classically, experiencing an increase when compared to cycles I and II. The results of learning Indonesian increased significantly when compared to Cycle I. Because in Cycle II the targeted KKM 70.00 had been achieved, this research was stopped until Cycle II. Based on the findings and theoretical studies that have been presented above, the writer can conclude that Jigsaw cooperative learning can increase the activity of teachers and students in the learning process, students' cooperative abilities and the results of learning Indonesian in class VII MTs Negeri 2 Kendari.